THE EFFECT OF SODIUM ALGINATE - CALCIUM CHLORIDE AS AN EDIBLE COATING ON WEIGHT LOSS, TPT AND COLOR OF FRESH CUT PEARS DURING COLD STORAGE - Paramita, Diva Julia; Muflihati, Iffah; Nurdyansyah, Fafa; Umiyati, Rini (Universitas Veteran Bangun Nusantara, 2026)
Pears (Pyrus pyrifolia) are tropical fruits with a sweet taste, crisp texture, and high water content. Cut pears have a short shelf life of 3-5 days due to enzymatic browning and physical damage after cutting. One method to extend shelf life is the use of edible coatings. This study aimed to test the effectiveness of sodium alginate and calcium chloride as coatings for cut pears in maintaining physical quality and extending shelf life. This study used a completely randomized design (CRD) with two factors: the first factor was sodium alginate concentration and the second factor was calcium chloride concentration. Pear coating was carried out by making a solution of sodium alginate and calcium chloride with concentrations of 1% and 2%, respectively. The coating process was carried out using the dipping method. The pears were washed and then peeled. The samples were then dipped in a sodium alginate solution for 2 minutes, and then dipped in a calcium chloride solution for 1 minute. Then the pears were stored at 4 Celcius degree and tested for 0, 6, and 12 days. Based on the results of the study, it showed that coating using sodium alginate and calcium chloride was able to suppress the increase in weight loss, total soluble solids, and maintain the color value of the pears. At a concentration of 2% sodium alginate and 1% calcium chloride, it had an effect on slowing down the decline in pear quality during storage. Keywords: Fresh Cut Pears, Edible Coating, Calcium Chloride, Pears, Sodium Alginate